Efficacy and safety of inotuzumab ozogamicin and its combination therapies in acute lymphoblastic leukemia: a systematic review and meta-analysis - Lao, Changtao; Wen, Jiange; Wen, Yuezhen (Frontiers in Oncology, 2025)
BackgroundAlthough treatment for acute lymphoblastic leukemia (ALL) has advanced considerably, adults with relapsed or refractory (R/R) disease continue to face a grave prognosis. Inotuzumab ozogamicin (InO), a CD22-directed antibody–drug conjugate, represents a promising development for B-cell ALL. This systematic review and meta-analysis aims to define the precise efficacy and safety profile of InO-based therapies—both monotherapy and combination regimens—in adults with newly diagnosed and R/R ALL.MethodsA systematic literature search was conducted in PubMed, Web of Science, Embase, the Cochrane Library, and clinical trial registries through 2 December 2024. The primary outcomes were overall response (OR), complete remission (CR), minimal residual disease (MRD) negativity, overall survival (OS), and the rate of stem cell transplantation (SCT). Secondary outcomes comprised adverse events (AEs) and relapse.ResultsThe meta-analysis included 1 randomized controlled trial (RCT), 14 single-arm studies, and 1 clinical trial, encompassing 1,068 patients. The pooled efficacy outcomes were as follows: OR rate:89.0% [95% confidence interval (CI): 85.8%–92.2%, 95% prediction interval (PI): 1.2%–99.9%; I2 = 90.1%, p<0.001], CR rate: 70.5% (95% CI: 58.6%–82.5%, 95% PI: 3.3%–76.9%; I2 = 94.0%, p<0.001), MRD− rate: 84.6% (95% CI: 79.5%–89.6%, 95% PI: 0.4%–99.8%; I2 = 80.9%, p<0.001), 1-year OS rate: 61.7% (95% CI: 44.9%–78.5%; I2 = 94.1%, p<0.001), 2-year OS rate: 51.4% (95% CI: 32.2%–70.7%; I2 = 93.8%, p<0.001), 3-year OS rate: 46.9% (95% CI: 22.5%–71.4%, 95%; I2 = 95.2%, p<0.001), 5-year OS rate: 44.9% (95% CI: 39.2%–50.5%, 95%; I2 = 0.0%, p =0.482), SCT rate: 27.5% (95% CI: 16.6%–38.4%, 95% PI: 1.2%–79.4%; I2 = 95.2%, p<0.001), relapse rate: 23.6% (95% CI: 16.6%–30.6%, 95% PI: 16.6%–99.6%; I2 = 78.2%, p<0.001), and incidence of veno-occlusive disease (VOD): 6.2% (95% CI: 3.8%–8.6%, 95% PI: 6.6%–54.5%; I2 = 68.0%, p<0.001).ConclusionInO demonstrates significant efficacy and a manageable safety profile in adult patients with ALL, supporting its use as a viable therapeutic option. Further randomized studies are needed to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024619042.